(untitled) (Mustansiria Dental Journal, 2018)
The purpose of the current study was to evaluate the calvarial thickness parameter in both genders, and in different skeletal patterns. The sample included 120 pretreatment digital lateral cephalometric radiographs of Iraqi subjects (60 males and 60 females) aged between 17 to 30 years, attending Orthodontic Clinic in the College of Dentistry; Baghdad University, and private clinics in Baghdad city. The 120 radiographs were divided into 3 groups (40 radiographs for each group) according to the ANB angles: ANB angle smaller than one degree (Class III), between two and four degrees (Class I), and larger than four degrees (Class II), each group was further subdivided into two subgroups according to gender (20 radiographs for each gender). Four linear measurements were used exclusively in the assessment of calvarial thickness parameter in both genders. The mean calvarial thickness values changed from highest to lowest in sphenoid, parietal, occipital, and frontal bones respectively. In the skeletal class II malocclusion the frontal and occipital bones’ thickness showed highly significant gender differences (P<0.01) using Student’s t- test, with females had thicker frontal bone than males, and males had thicker occipital bone than females, in addition the skeletal glass II group showed no significant gender difference (P>0.05) regarding sphenoid and parietal bones’ thickness. The most vital outcomes of the present study were the frontal and occipital bones can be used as important key bones for understanding the calvarial phenotypic description and sexual dimorphism in different skeletal patterns, while the sphenoid and parietal bones can be used as reference bones for standardization of cephalometric analysis.